1984
DOI: 10.1007/bf01711380
|View full text |Cite
|
Sign up to set email alerts
|

The role of the tubulointerstitial changes in the prognosis of IgA glomerulonephritis

Abstract: The authors investigated the tubulointerstitial changes (atrophic tubuli, interstitial fibrosis and round-cell infiltration) by two methods in renal biopsies from 56 patients with IgA glomerulonephritis. A statistically significant correlation was found to exist between the tubulointerstitial changes and serum creatinine level at the time of renal biopsy. A statistical significant correlation was also established between serum creatinine at the end of a period of 5 years of follow-up and tubulointerstitial cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have shown that fibrosis on biopsy is an index of functional renal impairment and a major determinant in the progression of chronic kidney disease [1,5,6,10-12,17]. Our findings emphasize that although fibrosis performs well overall, it is of less value for a subset of individual cases.…”
Section: Discussionmentioning
confidence: 50%
“…Several studies have shown that fibrosis on biopsy is an index of functional renal impairment and a major determinant in the progression of chronic kidney disease [1,5,6,10-12,17]. Our findings emphasize that although fibrosis performs well overall, it is of less value for a subset of individual cases.…”
Section: Discussionmentioning
confidence: 50%
“…For example, the clinical course of these patients was not uniform, i.e., some patients required chronic dialysis within 5-10 yr after onset, and the renal function of others slowly progressed to renal failure over a period of 20 yr after onset of the first symptoms. Variable histologic findings were also observed in the patients with progressive IgA nephropathy (42,45,46 In many chronic renal diseases, administration of an ACE inhibitor leads to a significant attenuation of proteinuria (16,49,50). Interestingly, it has been recently reported (51) that, in patients with insulin-dependent diabetes with normal renal function, the absence of the D polymorphism decreases the probability of development of microalbuminuria or proteinuria, but a strong correlation was not demonstrated in another study (52).…”
Section: Resultsmentioning
confidence: 99%
“…More often, glomerular lesions progress because of the destruction of glomeruli by crescents and/or by focal and segmental hyalinosis and sclerosis2. On the other hand, tubulointerstitial changes have been considered to play a role in the outcome of IgAN3, but the correlation between interstitial injury and declining kidney function has been vague. Recently, Cohen et al .…”
Section: Introductionmentioning
confidence: 99%